2022
DOI: 10.1021/acsbiomaterials.2c00247
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Matrix Biomolecules on Endometrial Epithelial Cell Attachment and Cytokeratin 18 Expression on Gelatin Hydrogels

Abstract: The endometrium undergoes profound changes in tissue architecture and composition, both during the menstrual cycle as well as in the context of pregnancy. Dynamic remodeling processes of the endometrial extracellular matrix (ECM) are a major element of endometrial homeostasis, including changes across the menstrual cycle. A critical element of this tissue microenvironment is the endometrial basement membrane, a specialized layer of proteins that separates the endometrial epithelium from the underlying endometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These endometrial perivascular cultures provide a platform to examine reciprocal crosstalk between the perivascular niche and trophoblast cells. Further, the engineered endometrial perivascular niche hydrogel can be combined with our recently reported methods for endometrial epithelial cell culture to establish a stratified endometrial model consisting of primary endometrial epithelial cells overlaying the perivascular niche (21). Combined, these elements of a stratified endometrial model offers significant potential to gain mechanistic insight into endometrial remodeling and changes in endometrial vascular networks in response to decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…These endometrial perivascular cultures provide a platform to examine reciprocal crosstalk between the perivascular niche and trophoblast cells. Further, the engineered endometrial perivascular niche hydrogel can be combined with our recently reported methods for endometrial epithelial cell culture to establish a stratified endometrial model consisting of primary endometrial epithelial cells overlaying the perivascular niche (21). Combined, these elements of a stratified endometrial model offers significant potential to gain mechanistic insight into endometrial remodeling and changes in endometrial vascular networks in response to decidualization.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, collagens I-IV alone or in combination with other ECM biomolecules increased HEMEC cell attachment on 2D microarrays compared to matrix combinations with Collagen V and the other endometrial associated ECM biomolecules (fibronectin, laminin, lumican, decorin, hyaluronic acid, tenascin C). Interestingly, two combinations we previously showed to increase endometrial epithelial cell (EEC) attachment (Collagen I + Collagen III, Collagen IV + Tenascin C) 14 also promoted high levels of HEMEC attachment, suggesting these combinations may be more universally important in the development of artificial endometrial models. Notably, collagen I alone resulted in the highest average HEMEC attachment per island which is not surprising because collagen I is the most prevalent collagen in the endometrium 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we systematically examine the combined role of endometrial-associated extracellular matrix stiffness, extracellular matrix ligand presentation, and angiogenic (VEGF) vs. stress-associated (cortisol) biomolecules on endometrial endothelial cell chirality. First, we define patterns of endometrial endothelial cell attachment and chirality in response to single and pairwise combination of 10 endometrial-associated 14 extracellular matrix (ECM) ligands using a high-throughput 2D array format. We report shifts in endometrial endothelial cells chirality using three separate metrics to describe polarization biases along one of three axes: 13 the left-right axis, apicobasal axis, or front-rear axis of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…26,52,53 There have also been significant developments in incorporating spatiotemporal control of multiple biomechanical factors in directing cellular fate. [54][55][56][57] Additional parameters such as three-dimensionality, substrate stiffness and viscoelasticity could be incorporated to develop a more biomimetic system that better reflects the complexity of the muscle microenvironment. 58,59 In conclusion, we have developed a stretchable tissue chip system to probe the combined effects of ECM composition and strain on myogenesis.…”
Section: Discussionmentioning
confidence: 99%